2023
DOI: 10.4093/dmj.2021.0306
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine Methyltransferase METTL3 Alleviates Diabetes-Induced Testicular Damage through Modulating TUG1/Clusterin Axis

Abstract: Background:The present study investigated the regulatory effects of N 6 -methyladenosine (m6A) methyltransferase like-3 (MET-TL3) in diabetes-induced testicular damage. Methods: In vivo diabetic mice and high glucose (HG) treated GC-1 spg cells were established. The mRNA and protein expressions were determined by real-time quantitative polymerase chain reaction, Western blot, immunofluorescence and immunohistochemistry staining. Levels of testosterone, blood glucose, cell viability, and apoptosis were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…[ 35 ] Notably, METTL3 is able to bind directly to m6A‐modified LINCRTUG1 to enhance the stability of LINCTUG1. [ 45 ] A recent study showed that METTL3 mediates telomeric repeat‐containing RNA m6A modification and promotes its stability via YTHDC1. [ 46 ] In this study, we discovered that METTL3 negatively regulates LINC01013 expression in hFOB1.19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] Notably, METTL3 is able to bind directly to m6A‐modified LINCRTUG1 to enhance the stability of LINCTUG1. [ 45 ] A recent study showed that METTL3 mediates telomeric repeat‐containing RNA m6A modification and promotes its stability via YTHDC1. [ 46 ] In this study, we discovered that METTL3 negatively regulates LINC01013 expression in hFOB1.19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…LINC00657, a long non-coding RNA, is gaining prominence for its potential roles in numerous living processes and illnesses. While its precise purposes are still being elucidated, emerging research suggests its involvement in complex cellular pathways ( Bhat et al, 2022a , Bhat et al, 2022b , Bhat et al, 2022c , Trewin et al, 2022 , Tian et al, 2023 , Zhou et al, 2023 ). Investigating LINC00657′s implications could provide valuable insights into its significance, potentially revealing its value as a diagnostic or therapeutic target in various health and disease contexts ( Wang et al, 2019 ).…”
Section: Tug1 and Diabetesmentioning
confidence: 99%
“…This work demonstrates how TUG1/clusterin signalling mediates the amelioration of diabetes-induced testicular damage by METTL3. ( Tian et al, 2023 ).…”
Section: Role Of Tug1 In Diabetes-associated Diseasesmentioning
confidence: 99%